The Effect of PMRI Approach Assisted by Baamboozle Media on Student Learning Outcomes in Arithmetic Sequences - Novila Yolanda; Indah Widyaningrum; Neni Lismareni (Universitas Islam Sultan Agung, 2025)
Abstract. This study aims to analyze the effectiveness of the Indonesian Realistic Mathematics Education (PMRI) approach assisted by Baamboozle media in improving students' learning outcomes in arithmetic sequences. An experimental method with a Pretest-Posttest Control Group Design was applied to 67 tenth-grade students at SMA Negeri 1 Jarai, divided into an experimental group (n=34) using PMRI with Baamboozle and a control group (n=33) with conventional instruction. Data were collected through written tests and analyzed using normality tests, homogeneity tests, and an independent t-test. The results indicated a significant improvement in the experimental group, with an average post-test score of 80, compared to the control group (70). Statistical analysis reinforced this finding (t = -7.136, p < 0.05), confirming that the integration of PMRI and Baamboozle not only enhanced learning outcomes but also fostered active student engagement. The implications of this study support the use of interactive digital media in context-based mathematics learning approaches.Keywords: PMRI, Baamboozle, arithmetic sequences, learning outcomes, mathematics education